The Reciprocal and Correlative Relationship Between Learning Culture and Online Education: A Case from Saudi Arabia - Hamdan, Amani K (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
The purpose of this paper is to build on the insights of educators regarding the relationship between culture and online learning. More specifically, this paper aims to explore the ways in which students’ culture of learning is changing as a result of the introduction of various modes of online learning. It also aims to explore the ways in which culture and cultural values affect the application and success of online-learning strategies. Particular attention is directed to learners’ perceptions of the advantages and disadvantages of online communication. The paper is based on primary data drawn from undergraduate female students’ responses regarding how online education is changing their learning culture and how their culture is influencing online education. Sixty-seven undergraduate Saudi female students participated in the survey. The literature in the field of online and distance education is explored to help answer these questions. The participants indicated that online education helped them to challenge some cultural norms, enhance their learning culture, and improve their communication skills.